Manajemen Sumber Daya Manusia pada Program Tahfidz Pendidikan Islam di Kota Bontang - Jannah, Baiq Faridatul; Khojir, Khojir; Rhendica, Rhendica (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2023)
Human Resources Management (HR) encompasses various crucial aspects of organizational management. One primary challenge involves recruiting and retaining high-quality talent. The objective of this research is to explore human resource management in relation to (1) the recruitment of human resources and (2) the development of human resources. This study adopts a descriptive qualitative approach to examine the human resource management practices at MTs Alam Al Hafidz and SMP IT Atsaqibiyah in Bontang City. Data collection methods include observation, interviews, and documentation. The data analysis technique employed is interactive analysis, consisting of data collection, condensation, presentation, and drawing conclusions. The research findings indicate that (1) meticulous recruitment and selection of human resources contribute to ensuring the engagement of high-quality teachers and staff in the educational process. (2) Investing in coaching for teachers is crucial to enhance their ability to teach and guide students in memorizing the Koran. This encompasses various aspects such as training, rights fulfillment, salary payments, communication, and skills.